EVALUATION OF INDOOR/OUTDOOR GAMMA EXPOSURE RATES AND EXCESS LIFE TIME CANCER RISK IN DIFFERENT CITIES OF PAKISTAN. Issue 4 (3rd September 2020) - Zeb, Jahan; Wasim, Mohammad; Awais, Muhammad; Ullah, Asad; Iqbal, Talat; Akhtar, Sheraz
Abstract: This study presents a detailed measurement of indoor and outdoor terrestrial gamma radiation levels in different cities of Pakistan. The measurements covered dwellings in 27 cities, covering all provinces and region of Azad Kashmir. Most of the houses were of attached type, made of brick walls and concrete roofs. The measurements were made by a handheld radiation survey meter containing Geiger–Muller tube. The average absorbed dose rate in air was 100 ± 32 nGy h −1 for indoor and 74 ± 30 nGy h −1 for outdoor. The population-weighted mean terrestrial dose rates were 90 nGy h −1 for indoor and 78 nGyh −1 for outdoor. The ratio of indoor to outdoor absorbed dose rate was 1.5 as compared to 1.3 for the world average. The estimated average annual effective dose rate was 0.58 ± 0.18 mSv a −1 and the mean excess life time cancer risk was 2.0 × 10 −3 .